Reduced presentations with fractures or orthopaedic infections to a major children's hospital during a national COVID‐19 elimination strategy. Issue 1 (9th November 2021) - Mason, Blair; Stott, Susan; Beamish, Rebecca
Abstract: Background: From 26 March 2020, New Zealand implemented a COVID‐19 elimination strategy which initially involved substantive limitations on public movement and assembly, and closure of non‐essential businesses. We asked what effect this had on acute paediatric orthopaedic presentations to a tertiary children's hospital. Method: The numbers, age and gender of patients with orthopaedic presentations, seen by either the Children's Emergency Department (CED) or the orthopaedic service during the study period, were compared with the equivalent 2019 period. Results: During the first 64 days of lockdown, 708 patients were seen in CED with orthopaedic presentations compared with 1124 patients in the same period in 2019 (37% reduction). We found a 55% reduction in musculoskeletal infections (from 135 to 61), a 40% reduction in total fractures (from 446 to 268) and a 27% reduction in soft tissue injuries (from 520 to 380). In 2020, similar proportions of patients were admitted for operating room procedures (15%) or had fractures reduced under sedation in CED (17%), however, increased numbers of soft tissue injuries were managed through CED under procedural sedation. Conclusion: A national COVID‐19 elimination strategy, closing all but essential businesses, limiting public movement, physical distancing and focusing on hand hygiene, led to reduced presentations not only with fractures and soft tissue injuries but also musculoskeletal infections. Increased numbers of patients had procedural sedation for soft tissue injuries, but there was no significant change in the proportion of patients admitted for surgery. Abstract : This article reviews the nature and frequency of paediatric orthopaedic fractures and infections presenting to a major tertiary hospital during New Zealand's COVID‐19 lockdown. We found a significant reduction in overall presentations, and a disproportionate reduction in orthopaedic infections.